The plateau effect in thermal conductivity of solid hydrogen with neon impurity: Quantum Crystals - Zholonko, N.N. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2007)
The thermal conductivity of solid hydrogen with 1–2 ppm Ne impurity was investigated in the temperature range 1.5–10 K on samples grown from the liquid phase at various growth rates. The result differ qualitatively from those obtained on samples grown from the gas phase: the thermal conductivity curve exhibited a dip in a broad plateau. The relaxation model is suggested to explain the effect supposedly due to linear impurity structures, arranged on dislocation lines. A comparison with the case of isolated neon atoms homogeneous distributed in the solid hydrogen is made.